A Systematic Review Exploring the Psychosocial Factors Affecting Adolescent Access to HIV Treatment Services - Tarique Variava; Jennifer Watermeyer (MDPI AG, 2022)
Context: Despite the global realization that increasing access to antiretroviral treatment promotes significant bio-medical gains amongst adolescents living with HIV (ALHIV), the psychosocial impact of HIV on the health and well-being of ALHIV has been overlooked. Objective: To identify, synthesize, and discuss the psychosocial factors that affect ALHIV who are accessing HIV treatment services in South Africa. Data sources: Only empirical research published in English were searched for via four electronic research databases (i.e., ProQuest, Web of Science, EBSCO, and Sabinet Online) of the University of the Witwatersrand on 1 August 2020. Eligibility criteria: Full-text articles published in English were included in the sample on the following basis: (1) the identified studies included HIV-positive adolescents (<semantics>≥</semantics>10 years old and <semantics>≤</semantics>19 years old) residing in South Africa; (2) the phenomena under investigation within the identified studies related to psychosocial factors which affect ALHIV accessing HIV treatment services in South Africa; (3) measures exploring any form of psychosocial factors associated with ALHIV in South Africa that had to be utilized; (4) study research designs were either an observational or cohort study; (5) studies were of a quantitative or qualitative nature, and (6) studies ought to have been published between 1 January 2000 and 31 July 2020. Data extraction: Data from the articles included in this systematic review were extracted using predefined data fields, including study quality indicators. Data synthesis: A total of 18 empirical articles met the inclusion criteria informing this research report. From the articles included in this systematic review, it was evident that ALHIV accessing HIV treatment services in South Africa were impacted by seven major psychosocial factors. Specifically, this included their (1) psychosocial development, (2) quality of life, (3) experience of adversity, (4) availability of social support, (5) experience of HIV stigma, (6) HIV status disclosure, and (7) adherence to ART. Conclusions: The physiological, social, behavioural, and cognitive functioning of ALHIV accessing HIV treatment services predisposed them to psychosocial distress, which in turn had implications for their health and well-being.